Islamic Value and Buying Intention Towards Suspecting Haram-Content Beverage Products in Islamic Countries: Developing a Conceptual Framework - Ahasanul Haque; Faruk Ahmed; SMH Kabir (Journal of Islamic Management Studies, 2022)
Islam has a positive effect on a human being for its comprehensive guidelines for showing both worldly and heavenly peace in life. Conventional ethics could not perfectly shape harmless, peaceful human behavior at work and in life because of its concentration on materialistic or worldly views. Fear to Almighty Allah protects human beings from doing work harmful to himself and others, whereas it is absent in conventional ethics because other religions permit alcoholism that influences people to violate every religious code for their worldly life. In another way, secular politics bounds alcoholic and non-alcoholic people with its worldly laws and regulations, and willingly or unwillingly slide them away from codes of religion. Islam can aid in avoiding suspected haram-content beverage products for its power of haram-halal codes since alcoholism is prohibited in Quran. According to Usul-Al-Fiq, pork and other animal fat used in various food and beverage products are harams since eating pork is listed in haram codes in Quran. In this study, a conceptual framework is developed to provide an insightful linkage between Islamic beliefs (personal, family, social, and institutional beliefs) and purchase intention towards haram-content suspected beverage products.